International guidelines on the study of glycated hemoglobin HbA1c level as a diagnostic criterion for diabetes mellitus and otherdisorders of carbohydrate metabolism - Gagik Radikovich Galstyan (Сахарный диабет, 2010)
Type 2 diabetes mellitus is rising at an epidemic scale throughout the world. Up to a certain moment, DM2 develops as a latent pathology which accounts for its late diagnosis and onset of therapy. Hence, the high frequency of vascular complications, early disablement and mortality. Therefore, the improvement of screening studies is of primary importance for the detection of metabolic disorders. At present, HbA1c determination is the most informative and cost-effective tool for the purpose. The choice of the method for measuring HbA1c is a paramount consideration. It must be standardized against a reference technique (high performance liquid chromatography) in conformity with the results of DCCT and UKPDS studies